Utilization of Local Resources for the Economy and the Importance of Education for Village Communities - Fatolosa Hulu; Fanny Corsby Sella Sarumaha; Gusman Waruwu; Fince Rahmat Yanto Halawa; Epafroditus Giawa; Trisaeli Hulu; Otolisasi Halawa; Andreas Meikardo Stevan Duha; Yamolala Zega (Universitas Muhammadiyah Makassar, 2026)
The utilization of local resources and educational empowerment are essential elements for achieving sustainable rural economic development, yet many villages still face limited capacity to transform local potential into productive economic activities. This study aimed to examine how community service activities integrating local resource utilization and educational awareness can enhance community empowerment and support village economic development. A qualitative descriptive approach was employed through a participatory community service program conducted in Mondrali Village, Idanogawo District, Nias Regency. Participants consisted of village officials, youth representatives, and community members selected purposively. Data were collected through interactive lectures, focus group discussions, role-play simulations, observations, and documentation, and were analyzed using thematic analysis to identify patterns of awareness, participation, and institutional readiness. The results showed three major findings. First, participants demonstrated increased understanding of value-added economic opportunities from natural resources, particularly through agro-processing initiatives. Second, awareness of human and cultural resources improved, reflected in proposals for cultural-based creative activities to support local income generation. Third, institutional readiness strengthened through discussions on establishing a village-owned enterprise to manage community-based businesses. Education emerged as a cross-cutting factor that enhanced motivation, leadership awareness, and collective action toward village development. This study contributes to the literature by demonstrating that participatory education integrated with local resource optimization serves as an effective initial strategy for sustainable rural empowerment. Practically, the findings provide a community service model that can support inclusive and context-based village economic development policies.